Analisis Prestasi Akademik, Pengalaman Magang, Kompetensi, dan Motivasi Kerja Terhadap Kesiapan Kerja Pada Mahasiswa Teknik Industri Universitas Gunadarma - Metha Audian Simanjuntak; Mohammad Abdul Mukhyi (CV. ITTC INDONESIA, 2025)
Amid globalization and accelerated industrial growth, the need for skilled, capable, and competitive human resources (HR) is increasingly urgent. Yet, Indonesia continues to grapple with high unemployment, low productivity, and gaps between graduates’ competencies and labor market requirements. This research investigates how academic performance, internship experience, competence, and work motivation shape the work readiness of Industrial Engineering students at Gunadarma University. Adopting a quantitative explanatory design, the study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. A total of 250 respondents were chosen via purposive sampling, limited to active students in semester six or above who had undertaken internships. The study’s outcomes are anticipated to contribute theoretically by expanding insights on determinants of work readiness, while offering practical value for students, universities, and industry in enhancing graduate quality and competitiveness.